Meningkatkan Pemahaman Konsep Bangun Ruang Mahasiswa Calon Guru Sekolah Dasar Menggunakan Game Android - Muhammad Erfan; Mohammad Archi Maulyda (PALAPA, 2020)
This study aims to improve the conceptual understanding of prospective elementary school teacher students on the concept of geometrical space which includes the relationship between lines and planes as well as lines and lines in geometrical space using Android games. The Android game used was XSection. This research is a quasi-experimental study with a pretest-posttest control group design. The sample in this study was taken using a cluster random sampling technique and obtained class 3C as an experimental class, namely the class that learns using Android-based educational games and 3D class as the control class, namely the class that learns without using Android-based educational games. Data regarding conceptual understanding were obtained by the multiple-choice tests and data were analyzed using independent sample t-test and normalized gain test. The results showed that the experimental class showed a significant increase in understanding the concept of geometrical space compared to the control class. The post-test average score of students' conceptual understanding in the experimental class was higher than the control class so that the Android-based education game was effective in improving students' understanding of the concept of geometrical space for prospective elementary school teachers.